The interplay between Th17 and T-regulatory responses as well as adipokines in the progression of non-alcoholic fatty liver disease - Świderska, Magdalena; Jaroszewicz, Jerzy; Stawicka, Agnieszka; Parfieniuk-Kowerda, Anna; Chabowski, Adrian; Flisiak, Robert (Clinical and Experimental Hepatology, 2017)
Non-alcoholic fatty liver disease (NAFLD) is a chronic progressive liver disease, coupled with metabolic syndrome, which may progress to non-alcoholic steatohepatitis (NASH). Diabetes, obesity, hypertension, hypercholesterolemia, and hypertriglyceridemia are considered to be the most common causes leading to the incidence of NAFLD. It is assumed that the accumulation of lipid deposits in hepatocytes leads to production of proinflammatory cytokines that triggers the development of liver inflammation. Regulatory T cells (Tregs) play a critical role in regulating inflammatory processes in NASH, while T helper type 17 (Th17) might functionally oppose Treg-mediated responses. In addition, important mediators of hepatic steatosis are fatty hormones known as adipokines. We aimed to describe the significance and interaction between Treg and Th17-related cytokines as well as adipokines in pathogenesis and its potential use as biomarkers of NAFLD, especially with respect to progression to NASH.